Bilingual Word Recognition in a Sentence Context - Van Assche, Eva; Duyck, Wouter; Hartsuiker, Robert J. (Frontiers in Psychology, 2012)
This article provides an overview of bilingualism research on visual word recognition in isolation and in sentence context. Many studies investigating the processing of words out-of-context have shown that lexical representations from both languages are activated when reading in one language (language-nonselective lexical access). A newly developed research line asks whether language-nonselective access generalizes to word recognition in sentence contexts, providing a language cue and/or semantic constraint information for upcoming words. Recent studies suggest that the language of the preceding words is insufficient to restrict lexical access to words of the target language, even when reading in the native language. Eyetracking studies revealing the time course of word activation further showed that semantic constraint does not restrict language-nonselective access at early reading stages, but there is evidence that it has a relatively late effect. The theoretical implications for theories of bilingual word recognition are discussed in light of the Bilingual Interactive Activation + model (Dijkstra & Van Heuven, 2002).